Proposed Strategy of Non Loan Earning Asset Portfolio Management For PT. Bank Rakyat Indonesia (Persero), Tbk. - Nabila Djunet, Ajeng; Sumirat, Erman (The Indonesian Journal of Business Administration, 2017)
Abstract. Indonesia banking industry profit according to Financial Services Authority report in 2015 only reached Rp104.6 trillion, down 6.76% from the position Rp112.2 trillion in the same period previous year. Moreover Bank Indonesia (BI) rates policy in downward trend, throughout 2015 BI has been reduced the deposit facility by 25 bps to 5.5% and continued in 2016 BI gradually reduce the rates to 4% as of November 2016. PT Bank Rakyat Indonesia (Persero) Tbk, as the most profitable bank in Indonesia, compared to peers still lacking in manage non-loan earning assets portfolio with high amount of placement with BI makes BRI lose the opportunity to gain more income. This problem can be solved by assessing alternative to increase non-loan earning assets return and performing a portfolio management of government bonds using passive and active strategies for yield enhancement and increase other comprehensive income. To measure the bond risk, duration quantify the relationship between bond price sensitivity to interest rate change. Non-loan earning asset portfolio management can be an alternative solution to maintain interest margin. The research suggested passive bond management to maintain held to maturity and available for sale portfolio. Active bond management can be used to maintain trading portfolio. Using sensitivity analysis, the strategies can increase weighted average yield of non-loan earning assets by 0.7%.Keywords: Bond Portfolio Management for Bank, Non- Loan Earning Asset, Duration